Adat and Islam: Examining the Sepasaran Tradition in Javanese Marriage in Boyolali Regency, Indonesia - Diana, Isna (At-Tafkir, 2024)
The Sepasaran tradition, held five days after a wedding, is an important custom in the community of Kembangkuning Village, Cepogo Subdistrict, Boyolali District. This tradition carries deep cultural and religious significance, fostering social bonds in the midst of changing times. As part of the tradition, a thanksgiving event (kendurenan) is organized, followed by the symbolic acknowledgment of those who helped with the wedding preparations. This study explores how the Sepasaran tradition is practiced in Kembangkuning Village and analyzes it through the lens of 'Urf in Islamic thought. The research adopts a qualitative approach, utilizing interviews and documentation to gather data. The findings reveal that the Sepasaran tradition serves as an expression of gratitude and a prayer for blessings following the wedding ceremony. From the perspective of 'Urf, this tradition is classified as 'Urf Amali because it is practiced consistently and widely accepted by the local community. It is also categorized as 'Urf Shahih because it aligns with Islamic principles and as 'Urf Khas due to its specific regional context. This study demonstrates that the Sepasaran tradition remains a meaningful and relevant practice in the community, reflecting local wisdom and a harmonious relationship between culture and religion. It highlights how the tradition continues to strengthen social ties while staying in harmony with Islamic values